2012
DOI: 10.1590/s0100-40422012000600011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chitosan microparticles containing curcumin and crosslinked with sodium tripolyphosphate produced by spray drying

Abstract: Recebido em 21/8/11; aceito em 11/1/12; publicado na web em 15/5/12The aim of this study was to encapsulate curcumin into chitosan, using sodium tripolyphosphate (TPP) as an ionic crosslinker by the spray drying method. The influence of TPP on the properties of the final product, such as solubility, morphology, loading efficiency, thermal behavior, swelling degree and release profiles, was evaluated. The microparticles had a spherical morphology (0.5-20 µm) with no apparent porosity or cracks. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 31 publications
(48 reference statements)
4
35
0
4
Order By: Relevance
“…developed polymeric nanoparticles containing quercetin, and in vitro studies on the sequestering ability of DPPH radicals demonstrated that the antioxidant activity of the nanoparticles was greater than that of free quercetin. Parize et al . demonstrated that chitosan microparticles containing curcumin had a higher antioxidant activity (33%), which was measured by DPPH radicals, than chitosan films and microspheres containing curcumin.…”
Section: Resultsmentioning
confidence: 99%
“…developed polymeric nanoparticles containing quercetin, and in vitro studies on the sequestering ability of DPPH radicals demonstrated that the antioxidant activity of the nanoparticles was greater than that of free quercetin. Parize et al . demonstrated that chitosan microparticles containing curcumin had a higher antioxidant activity (33%), which was measured by DPPH radicals, than chitosan films and microspheres containing curcumin.…”
Section: Resultsmentioning
confidence: 99%
“…The microparticles were separated by centrifugation at 3000 rpm for 15 min, and drug encapsulation efficiency (EE) of the microparticles was evaluated by measuring the absorption of the supernatant liquid using UV spectrophotometer at 425 nm (k max of CUR) (Parize et al 2012;Mukerjee and Vishwanatha 2009;Benetton et al 1998). The supernatant was collected at different intervals, three samples were taken, and the mean value and standard error were calculated.…”
Section: Evaluation Of Encapsulation Efficiencymentioning
confidence: 99%
“…3a) are at 3363 cm −1 related to\ \OH stretching, at 2877 cm −1 related to the CH stretching, at 1658 cm −1 related to the C_O bond of amide I, at 1593 cm −1 related to the deformation vibration of the NH primary amine, at 1419 cm −1 related to the CH 2 bond, at 1377-1257 cm −1 associated with the CN bond, at 1153 cm −1 related to the stretching of the C\ \O\ \C bond of glucose and β 1-4 bands at 1072 and at 1029 cm −1 corresponding to the vibration of the angular deformation of the amino group [36][37][38].…”
Section: Infrared Spectroscopy (Ftir)mentioning
confidence: 99%